THE VALIDITY OF THE LAND SELLING AGREEMENT WHICH CONTAINS LEGAL DEFECTS - Agra Verta Ardi Nugraha (SEAN Institute, 2020)
A valid agreement must be made based on the provisions of Article 1320 of the Civil Code, these conditions include subjective and objective conditions as contained in Article 1320 of the Civil Code. An agreement made that does not fulfill one of the requirements of Article 1320 of the Law has different legal consequences. An agreement that does not meet the subjective requirements of Article 1320 of the Civil Code has legal consequences, a cancellation of the agreement may be requested by one of the parties, while an agreement that does not meet the objective requirements of Article 1320 has legal consequences for the agreement made by these parties. null and void and deemed to have never occurred. The land sale and purchase agreement made by the late Ibrahim and Djaidin to Nur Saidah is an agreement made using false information by the late Ibrahim and Djaidin as contained in Decision Number: 178/PDT.G/2012/PN.Sda. The late Ibrahim and Djaidin in the case of the decision acted as heirs of Anuwar P. Sidik to sell the inheritance land that had not been divided by inheritance, as the legal facts found that the late Ibrahim and Djaidin were not heirs of Anuwar P. Sidik. Based on the case, there are interesting things that want to be studied in writing this thesis, namely, the sale and purchase agreement must include the identity of the seller and buyer.